RECONSTRUCTION OF RARE CRANIOFACIAL CLEFTS: AN EARLY EXPERIENCE - Ullah, Tahmeed; Bilal, Muhammad; Haq, Naseem ul; Abenavoli, Fabio (Journal of Postgraduate Medical Institute, 2011)
Objective: Proper assessment and referral of these rare craniofacial clefts to plastic surgeon in necessary for the optional surgical outcome. We achieved good results in all the cases regarding soft tissue defects. No surgical intervention was performed for bony defects. The study was and conducted at the department of plastic and reconstructive surgery, Hayatabad Medical Complex Peshawar and Al-Shifa Health Care Center Peshawar, from January 2008 to December 2009. A total of 08 patients with rare craniofacial clefts were treated. Diagnosis was based on clinical examination and radiographic findings on CT scan. Tessier's classification was used to describe these clefts. There were two case of unilateral cleft 7, two cases of bilateral cleft 7, two cases of cleft 30, one case of bilateral cleft 4 and a single case of proboscis lateralis. All the patients were treated surgically and the different clefts were repaired or reconstructed executing different procedures. To share our experience regarding the management of rare craniofacial clefts.